Determination of tetracycline dose in treatment of advanced periodontitis - Tabatabaei E.; Rokn AR (Tehran University of Medical Sciences, 1999)
This study is for appointment the dose of systemic 4 groups of patients selected for this study."nFirst group had sealling, root planing and planing and periodontal surgery and no drugs. Second group"nhad sealling, root planing and periodontal surgery with 1 gr per day of tetracycline for two weeks and"nthird group for 3 weeks and fourth group for 4 weeks."nThe fourth group was.the best clinical improvement. The indexes were PPD, CAL, PI, GI.